Pengolahan Kelapa Menjadi Virgin Coconut Oil (VCO) dengan Metode Fermentasi Sederhana - Nury, Dennis Farina; Fahni, Yunita; Yuniarti, Reni; Achmad, Feerzet; Deviany; Variyana, Yeni (Journal of Industrial Community Empowerment, 2023)
Coconut plant is frequently referred to as the plant of life since every part of it may be utilized and turned into a product. One of the commercial processed product by coconut is virgin coconut oil (VCO), which has many benefits to health properties. VCO is extracted from coconut milk from coconut fresh. The introduction of virgin oil (VCO) to partners aimed about VCO's advantages and development of appropriate technology that can be applied to local communities in Negeri Katon, Lampung Selatan. This community service activity program introduced fermentation method using yeast to convert coconut milk into VCO. The activity were conducted in three steps: i.e presentation of VCO process production and discussion, demonstration of making VCO together, and evaluation based on pre and post-test form results. Several analysis have been conducted including the percentage yield, density, viscosity and pH of the VCO. The evaluation of this activity was obtained from pre and post-test results. The results of the pre-test showed that among 50% the people of Negeri Katon really needs to the activity of making VCO by fermentation together. Based on the highest post-test result of 91%, it can be concluded that the VCO-making activities are very useful. Further development of activities, such as intensive practice in making VCO and training in packaging and selling VCO is very needed. Based on the results obtained, it can be concluded that the activity of making VCO by fermentation for the community of Negeri Katon is very necessary to be carried out in terms of utilizing coconut into VCO and creating business opportunities for the future.